An analysis of the causality effect of exchange rate and interest yields: a case study of Zambia - Bwalya, Obed (Research of GSB, 2017)
This study analyses the relationship between the US Dollar/Zambian kwacha exchange rate and the interest rate yields on the 91-day and 182-day T-bills in Zambia. Using statistical analysis of regression analysis and co integration, the study found that a long-run relationship does not hold for both 91-day and 182-day T-bills taken for any corresponding set of interest rate and exchange rate respectively. Nonetheless, the three variables taken simultaneously demonstrated that a long-run correlation exist. Following a comprehensive analysis of the results from this study, it is concluded that the statistical relationship that exists is not very significant and investors looking forward to invest in Zambia's financial markets should include other factors in order to forecast the exchange rates with regard to the changes in interest rates.